(untitled) (Vietnam Journal of Community Medicine, 2022)
Objectives: Evaluate of the results of Crossen surgery method to treat genital prolapse at Nghe An Obstetrics and Pediatrics Hospital. Subjects-methods: Cross-sectional description of all patients with grade II, grade III genital prolapse who underwent Crossen surgery method at Nghe An Obstetrics and Pediatrics Hospital. Result: The mean surgery time was 69.4 ± 15.7 minutes. Average time after surgery 6.1 ± 2.1 days. The rate of postoperative complications is 10% including fever and urinary retention after surgery. All patients were discharged in stable health, in which good condition accounted for 80%. Conclusions: Crossen surgery method is feasible and safe. The method has a short operative time and low complication rate.